The Impact of Acknowledgment in the Civil Transactions System: A Comparative Study - Amer Kenan Alntaifat (International Journal of Law Research and Studies, 2024)
The study aimed to explore the evidentiary basis of acknowledgment in Islamic jurisprudence and legal systems, highlighting the importance of safeguarding wealth by acknowledging people’s rights. It examined the procedures prescribed by the legislator to ensure the legal effects of acknowledgment and clarified the relationship between jurisprudence and the legal system regarding the rights arising from acknowledgment. The researcher adopted the inductive method by analyzing rulings on acknowledgment in Islamic jurisprudence, the descriptive method by citing and attributing jurists’ opinions, and the analytical method by interpreting and comparing these opinions. The study concluded that acknowledgment is validated by the Qur’an, Sunnah, consensus, and analogy. In law, acknowledgment is absolute evidence, though limited to the disputing parties, and its evidentiary weight varies depending on whether it is judicial or extrajudicial. Judicial acknowledgment, made before the court during relevant proceedings, is conclusive evidence against the acknowledger, while extrajudicial acknowledgment occurs outside the court or in unrelated disputes. Legal provisions regarding acknowledgment align with Islamic conditions concerning the acknowledger, the recipient, the acknowledged right, and its formulation. The study also addressed solidarity, noting that when multiple debtors are jointly liable, each is fully responsible for the entire debt toward the creditor, with the paying debtor entitled to seek reimbursement from others according to their shares.